Portumna Dominican Friary, west door, jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
West door jamb, arch and hood. Moulding from intrados comprises: hollow, fillet, roll-and-fillet, fillet, hollow. The hood, which is placed far from the jamb, comprises from outer to inner face: frontal fillet, hollow, right-angled rebate, hollow.
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Dominican; Gothic doorways; Late Medieval; roll-and-fillet moldings; fillets (moldings); moldings, hollow; hood moldings